Postexercise glucose-fructose coingestion augments cycling capacity during short-term and overnight recovery from exhaustive exercise, compared with isocaloric glucose - Gray, E. A.; Green, T. A.; Betts, J. A.; Gonzalez, J. T. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
During short-term recovery, postexercise glucose-fructose coingestion can accelerate total glycogen repletion and augment recovery of running capacity. It is unknown if this advantage translates to cycling, or to a longer (e.g., overnight) recovery. Using two experiments, the present research investigated if postexercise glucose-fructose coingestion augments exercise capacity following 4-hr (short experiment; n = 8) and 15-hr (overnight experiment; n = 8) recoveries from exhaustive exercise in trained cyclists, compared with isocaloric glucose alone. In each experiment, a glycogen depleting exercise protocol was followed by a 4-hr recovery, with ingestion of 1.5 or 1.2 g·kg-1·hr-1 carbohydrate in the short experiment (double blind) and the overnight experiment (single blind), respectively. Treatments were provided in a randomized order using a crossover design. Four or fifteen hours after the glycogen depletion protocol, participants cycled to exhaustion at 70% Wmax or 65% Wmax in the short experiment and the overnight experiment, respectively. In both experiments there was no difference in substrate oxidation or blood glucose and lactate concentrations between treatments during the exercise capacity test (trial effect, p > .05). Nevertheless, cycling capacity was greater in glucose + fructose versus glucose only in the short experiment (28.0 ± 8.4 vs. 22.8 ± 7.3 min, d = 0.65, p = .039) and the overnight experiment (35.9 ± 10.7 vs. 30.6 ± 9.2 min, d = 0.53, p p = .026). This is the first study to demonstrate that postexercise glucose-fructose coingestion enhances cycling capacity following short-term (4 hr) and overnight (15 hr) recovery durations. Therefore, if multistage endurance athletes are ingesting glucose for rapid postexercise recovery then fructose containing carbohydrates may be advisable.